2014
DOI: 10.1557/jmr.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

Identification of optimal solar fuel electrocatalysts via high throughput in situ optical measurements

Abstract: Many solar fuel generator designs involve illumination of a photoabsorber stack coated with a catalyst for the oxygen evolution reaction (OER). In this design, impinging light must pass through the catalyst layer before reaching the photoabsorber(s), and thus optical transmission is an important function of the OER catalyst layer. Many oxide catalysts, such as those containing elements Ni and Co, form oxide or oxyhydroxide phases in alkaline solution at operational potentials that differ from the phases observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 49 publications
(70 reference statements)
0
20
0
1
Order By: Relevance
“…The optical transmission efficiency (α T,cat , see Experimental Section) was calculated as the fraction of the transmitted photons over 390− 600 nm (the primary BiVO 4 absorption range), as previously described in greater detail. 48 We previously reported the OER catalytic activity in pH 14 electrolyte, 44 revealing similar activity in the Ni 0.25 Co 0.25 Ce 0.5 O x and Ni 0.6 Fe 0.4 O x composition regions. In pH 13 electrolyte, as used in the present study, the best electrocatalytic activity is found in the (Ni−Fe−Co)O x pseudoternary composition space and is more Ni-rich with Ni 0.7 Co 0.1 Fe 0.2 O x being the optimal catalyst (see Figure S5).…”
Section: Resultsmentioning
confidence: 71%
“…The optical transmission efficiency (α T,cat , see Experimental Section) was calculated as the fraction of the transmitted photons over 390− 600 nm (the primary BiVO 4 absorption range), as previously described in greater detail. 48 We previously reported the OER catalytic activity in pH 14 electrolyte, 44 revealing similar activity in the Ni 0.25 Co 0.25 Ce 0.5 O x and Ni 0.6 Fe 0.4 O x composition regions. In pH 13 electrolyte, as used in the present study, the best electrocatalytic activity is found in the (Ni−Fe−Co)O x pseudoternary composition space and is more Ni-rich with Ni 0.7 Co 0.1 Fe 0.2 O x being the optimal catalyst (see Figure S5).…”
Section: Resultsmentioning
confidence: 71%
“…discovery and deployment underscores the immediate impact of HTE, 104 and as recently demonstrated by combinatorial integration of catalysts into solar fuels photoanodes, fabrication of device components can yield surprising discoveries and enhancements in performance. 110,111 The suite of HTE techniques in the catalysis field comprise perhaps the most advanced technology for rapid characterization of surfaces and interfaces, which directly addresses the key recommendations from the HTE workshop. 16 An added benefit of the use of HTE is the potential to explore atypical catalyst-support formulations, which can result in significant increases in both catalytic performance and mitigation of deactivation mechanisms, an often overlooked aspect of catalyst design.…”
Section: Catalystsmentioning
confidence: 99%
“…Therefore, in theoretical calculations the optimal catalyst loadings often occur at ultra-thin (< 1 nm) film thicknesses, for which the optical obscuration of the catalyst films is reduced. 18,22 For the electrodes that utilize uniformly coated catalyst films, improvement of the transparency of the electrocatalyst films, such as microstructuring porous Pt films, 23 is an effective strategy to increase the optimal loading of the electrocatalysts and hence increase the optimal STH conversion efficiency of the cell. …”
Section: A Comparison Between the Sth Conversion Behavior Of Patternmentioning
confidence: 99%